Histopathological Efficacy of Docetaxel Versus Paclitaxel As First Line Chemotherapy for Epithelial Ovarian Carcinoma - Şimşek, Tayyup; Yılmaz, Arif; Erdoğan, Gülgün; Peştereli, Elif (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: To evaluate and compare efficacy of docetaxel and paclitaxel combining with carboplatin in the first line chemotherapy of epithelial ovarian carcinoma according to hystopathological findings of second look laparatomy. STUDY DESIGN: Thirty two patients having stage II-IV epithelial ovarian cancer (17 cases in the paclitaxel-carboplatin group,15 cases in the docetaxel-carboplatin group) and operated in Department of Obstetrics and Gynecology, Division of Gynecologic Oncology were entered in this study. The cases were randomized for the treatment. All cases had inform-consent about the treatment options and second look procedures. The cases who completed chemotherapy and had a second look laparatomy were included the study. Pathological responses were evaluated with second look findings proved with biopsy. Statistical analyses were performed with Chi square and Mann-Whitney U tests. Survival analyses were calculated with using Kaplan-Meier survival analyses and Log Rank test. P>0.05 was accepted for statistical significance. RESULTS: There were no differences in demographic characteristics and rate of optimal cytoreduction between two groups. Eight cases (47,1%) in the paclitaxel-carboplatin group and 3 cases (20%) in the docetaxel-carboplatin group were hystopathological tumor positive in the second look operation without statistically significance. Also there was no significant difference between two groups in mean survival time(p 0.06). CONCLUSION: Efficacy of docetaxel and paclitaxel are the same in terms of hystopathological findings of second look laparatomy in the treatmet of first-line epithelial ovarian cancer.